Alimentation Et Construction De L’idéal Du Corps : Le Culte De La Minceur Chez Les Abidjanais (Côte d’Ivoire) - Atse Achi Amédée-Pierre; Goubo Siméon; Hien Lewa (European Scientific Journal, ESJ, 2016)
This study analyzes the weight control strategies in Abidjan and the issues that motivate them. The study covers 400 Abidjanes from 18 to older, including 05 persons mainly from the medical corps. From the quantitative and qualitative approaches focused respectively on a survey and open interviews, focus groups and direct observation, the results show that the cult of thinness gradually became fad, so that young people and adults seniors are the faithful. weight control strategies are structured primarily around food restriction and not sedentary. Implicit issues such efforts are among others seeking health and esthetics or beauty of the body. Despite these efforts, most of the faithful of the thinness of Abidjan lapse back into the overweight and obesity because sport and thought food restriction as effective ways to lose weight can not achieve their objective (thinness) and long term.